2010
DOI: 10.1111/j.1743-6109.2009.01641.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of 17β-Hydroxysteroid Dehydrogenase 3 and the Risk of Hypospadias

Abstract: Introduction Hypospadias is a common congenital anomaly caused by incomplete fusion of urethral folds. Development of the urethra and external genital system in the male fetus is an androgen-dependent process. In this regard, enzymes 17β-hydroxysteroid dehydrogenase type 3 (17βHSD3, encoded by HSD17B3) and steroid 5α-reductase type 2 (encoded by SRD5A2) play crucial roles. Aim To investigate the possible associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 62 publications
2
28
1
Order By: Relevance
“…The highest inhibitory potency was seen for 20␣-dihydrodydrogesterone, with dydrogesterone and progesterone having lower actives. Recently, genetic polymorphisms of S289 of HSD17B3, which lead to lower expression levels, have been related to an increased risk of hypospadias [42]. These data suggest that inhibition of 17␤-HSD type 3 can also affect fetal development.…”
Section: Discussionmentioning
confidence: 92%
“…The highest inhibitory potency was seen for 20␣-dihydrodydrogesterone, with dydrogesterone and progesterone having lower actives. Recently, genetic polymorphisms of S289 of HSD17B3, which lead to lower expression levels, have been related to an increased risk of hypospadias [42]. These data suggest that inhibition of 17␤-HSD type 3 can also affect fetal development.…”
Section: Discussionmentioning
confidence: 92%
“…In a study of 633 hypospadias cases, significant association of 4 SNPs and 2 haplotype blocks in HSD17B3 was found [Carmichael et al, 2014] (table 1). In a Japanese study of 89 hypospadias patients and 291 controls, the researchers found that in subjects carrying homozygous HSD17B3 +913A alleles (289S) the risk of hypospadias was significantly higher, including the risk of severe hypospadias [Sata et al, 2010] (table 1). They found that the mRNA expression levels of this form of HSD17B3 were lower, suggesting this polymorphism may be a risk modifier for hypospadias [Sata et al, 2010].…”
Section: Androgens and Hypospadiasmentioning
confidence: 99%
“…We found no association of the SRD5A2 gene with the disease of severe and/or mild hypospadias in our Caucasian population. The previously reported variants associated with hypospadias in either Caucasians or patients from other populations [Silver and Russell, 1999;Wang et al, 2004: Thai et al, 2005van der Zanden et al, 2010;Sata et al, 2010] may be explained by the ethnic group differences (in the cases where ethnicity differed from our studied population) and/or simply by the insufficient number of individuals investigated in each study. So far, we have investigated the largest cohort of cases and controls with regards to the SRD5A2 gene.…”
Section: Discussionmentioning
confidence: 75%
“…At that time, the disorder was molecularly characterized which first led to the cloning of the SRD5A2 gene and, subsequently, led to the identification of over 22 mutations, all of which were found to reduce the activity of the enzyme [Thigpen et al, 1992;Wigley et al, 1994]. Later on, several smaller studies found 2 SNPs (rs523349 (V89L) and rs9282858 (A49T)), located in exon 1 of the SRD5A2 gene, to be associated with hypospadias (the milder form of 46,XY disorder of sex development), whereas other minor studies were not able to find any connection between these particular SNPs and the studied disease [Silver and Russell, 1999;Wang et al, 2004;Thai et al, 2005;van der Zanden et al, 2010;Sata et al, 2010]. In our present study, we investigated hypospadias cases and controls using an optimal set of haplotype tagging SNPs covering the entire SRD5A2 gene, thus, capturing all haplotypes with a frequency above 5%, including those encompassing the 2 variants described above.…”
Section: Discussionmentioning
confidence: 99%